Konseling Kelompok Teknik Behavior Contract Untuk Mengurangi Perilaku Terlambat Datang Ke Sekolah Di Sman 18 Surabaya: Counseling Group Behavior Contract Technique to Reduce Late Behavior Coming to School at SMAN 18 Surabaya - Lailatusa'adah; Bakhrudin All Habsy; Nurudducha (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This study aims to determine the effectiveness of group counseling with behavior contract techniques to reduce the behavior of late coming to school of students of SMAN 18 Surabaya. This research is a type of Guidance and Counseling Action Research (PTBK) with qualitative methods conducted in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The research subjects consisted of four students who were recorded as tardy seven to thirteen times in one month based on documentation data of tardiness records. Data collection was conducted through observation, interviews, and documentation of students' tardiness records at school. In the first cycle, the results of group counseling showed that tardiness reduced to 2-3 times a week. In the second cycle, there was a significant decrease where no learners were late because they already had a strong commitment to comply with the agreed behavior contract. The results of this study indicate that group counseling techniques using behavioral contracts are effective in reducing the behavior of coming late to school at SMA Negeri 18 Surabaya. Keywords: Behavior Contract Group Counseling, Late Behavior